PENGARUH PENGGUNAAN MULTIMEDIA INFOGRAFIS INTERAKTIF TERHADAP MOTIVASI DAN KETERLIBATAN BELAJAR SISWA PADA PEMBELAJARAN IPAS DI SDN 26 TOLITOLI - Risa Rahmawati, Karmila; Hamna; Mustakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student motivation and engagement are important aspects in supporting the success of the learning process. Learning methods and media are also key components in successful learning. The problem is the low level of student motivation and engagement in learning at SDN 26 Tolitoli in IPAS learning. To overcome this problem, the researcher conducted a study by applying interactive multimedia infographics. The purpose of this study was to determine the effect of interactive multimedia infographics on student motivation and engagement in IPAS learning at SDN 26 Tolitoli. This study used a quantitative pre-experimental approach with a one-group pretest-posttest design. The instruments used were observation sheets and questionnaires with a sample size of 22 fourth-grade students at SDN 26 Tolitoli, using purposive sampling. The data analysis techniques used were the Paired sample t-test and the N-Gain test. The results of the Paired Sample t-test and reinforced by the N-Gain test showed that the sig value was 0.000 < 0.05 for motivation, while the involvement sig value was 0.001 < 0.05, meaning that it was significantly different even though it was in the low category. It can be concluded that the use of interactive infographic multimedia has an effect on student motivation and learning involvement.